Reaching for the Edge I: probing the outskirts of massive galaxies with HSC, DECaLS, SDSS, and Dragonfly. Issue 4 (29th July 2022) - Li, Jiaxuan; Huang, Song; Leauthaud, Alexie; Moustakas, John; Danieli, Shany; Greene, Jenny E; Abraham, Roberto; Ardila, Felipe; Kado-Fong, Erin; Lokhorst, Deborah; Lupton, Robert; Price, Paul
ABSTRACT: The outer light (stellar haloes) of massive galaxies has recently emerged as a possible low scatter tracer of dark matter halo mass. To test the robustness of outer light measurements across different data sets, we compare the 1D azimuthally averaged surface brightness profiles of massive galaxies using four independent data sets: the Hyper Suprime-Cam survey (HSC), the Dark Energy Camera Legacy Survey (DECaLS), the Sloan Digital Sky Survey (SDSS), and the Dragonfly Wide Field Survey (Dragonfly). We test the sky subtraction and proposed corrections for HSC and DECaLS. For galaxies at z < 0.05, Dragonfly has the best control of systematics, reaching surface brightness levels of μ r ≈ 30 mag arcsec −2 . At 0.19 < z < 0.50, HSC can reliably recover individual surface brightness profiles to μ r ≈ 28.5 mag arcsec −2 ( R = 100–150 kpc in semimajor axis). In a statistical sense, DECaLS agrees with HSC to R > 200 kpc. DECaLS and HSC measurements of the stellar mass contained within 100 kpc agree within 0.05 dex. Finally, we use weak lensing to show that measurements of outer light with DECaLS at 0.19 < z < 0.50 show a similar promise as HSC as a low scatter proxy of halo mass. The tests and results from this paper represent an important step forward for accurate measurements of the outer light of massive galaxies and demonstrate that outer light measurements from DECam imaging will be a promising method for finding galaxy clusters.